INFLUENCE OF PROBIOTICS, INTRODUCED IN THE COMPOSITION OF THE FEED SUBSTRATE, IN PARTICULAR HEMATOLOGICAL INDICATORS OF CARASSIUS GIBELIO BLOCH - Vasina, Liliia (Biological systems, 2022)
Significant anthropogenic influence, the emergence of a large number of pollutants of various origins create an ad- verse effect on the vital activities of organisms inhabiting water bodies. Often, the consequence of such impacts is a violation of the qualitative and quantitative composition of the microbiota - the autochthonous specific water body and the one that forms the microbiocenosis of the organism of aquatic animals, which leads to the development of diseases. Recently, the number of studies indicating the positive effect of the use of probiotics as preventive, therapeutic agents and biological factors affecting water quality has been increasing. Probiotic microorganisms not only perform a pro- tective function against pathogens through the production of short-chain fatty acids, bacteriocins, lysozyme, hydrogen peroxide, but also synthesize numerous enzymes and metabolites to provide digestive, regulatory, trophic, immunomod- ulatory and immunostimulatory functions. The range of studied probiotics is represented not only by microorganisms traditional for aquaculture (for example, Bacillus), but also by representatives of the genus Lactobacillus, the presence of which is recorded in individual biotopes of fish. We have studied the effect of Lactobacillus сasei probiotic microor- ganisms introduced into the feed on some individual hematological indicators of Carassius gibelio Bloch and analyzed changes in general behavioral indicators under the influence of modified feed. The effect of probiotics was studied after 15-day acclimatization of fish in aquariums. It has been proven that the introduction of probiotics as part of the feed substrate for 28 days has a positive effect on rapid adaptation to external stress factors, stabilization and weight gain of fish, physiological state of external mu- cous membranes, behavior and general condition of fish, which may indirectly indicate the role of probiotics in mobili- zation of body systems in the event of a change in living conditions. An increase in the number of leukocytes, an in- crease in the level of phagocytic activity of neutrophils, in particular the phagocytic index, was noted, which confirms the direct effect of probiotics in increasing the body's reactivity.
Keywords: Lactobacillus сasei; Carassius gibelio Bloch; probiotics; leukocytes; phagocytic activity